Micropollutants Identification Affecting the Nearby Environment from Highway Runoff: The Case Study of Cyprus Highway - Antonis A. Zorpas; Lampis A. Ilia; Irene Voukkali; Vassilis Inglezakis (Journal of Chemistry)
Road/highway surfaces accumulate significant quantities of pollutants including nutrients, heavy metals, and polycyclic hydrocarbon aromatic (PHAs). Traffic characteristics (vehicle speed, traffic load, etc.), climate, long dry wet periods, and rainfall event intensity and duration are regarded as important factors in generating pollutants in high way runoff (HRO). Regarding rainfall control, most of the road is served by drainage ditches which collect the runoff and direct it to the nearest natural water courses. This paper focuses on the estimation of pollutant that is coming from two several highways (to the airport and to the biggest industrial area) in Cyprus. Overall, more than 100 different samples were collected and analysed over a period of two years. Several parameters were determined like PHA, COD, electronic conductivity (EC), total suspended solid (TSS), total dissolved solid (TDS), pH, fats and oils (FOG), T. Coliforms, NO3, NO2, NH4, SO4, Cl, As, Ba, Bi, Cd, Co, Cr, Cu, Fe, Hg, Mn, Mo, Ni, P, Pb, and Zn. The results indicated that the first flush consists of major pollution due to the fact that all parameters are in high levels. As the rainfall continues the pollution decreases but the influence to the nearby areas of the runoff is high.